Assesment of Forensic Children Cases Applying to the Emergency Service of Başkent University Ankara Hospital - Büken, Erhan; Yaşar, Zehtiye Füsun (The Bulletin of Legal Medicine, 2015)
Objective: This study has been carried out in order to determine the demographic properties, application reasons and qualifications of the legal reports prepared of the forensic cases in the group of 0-18 ages that applies to the Emergency Service of Başkent University Ankara Hospital and to compare the data obtained with similar studies.Materials and Methods: Sample of this study which has a descriptive characteristic is compose of 2397 forensic notification reports prepared between the dates of 01/01/2013-31/12/2013 in the Emergency Service of Başkent University Ankara Hospital. The study includes the evaluation of664 reports of the children.Results: The cases of children between 0-18 years who applied to Children Emergency Service constitute 27,70% of all forensic reports. 316 (45,0%) of the children are girls and 348 (49,5%) are boys. The highest rate of the cases is seen in 0-6 year group with 402 (50,54%) children. When we look at the distribution of the ty pe of the case regardless the gender, it is observed that the emergency services are applied for bum cases at most (n:218,32,83%) and this is respectively followed by the poisoning (n: 119, 17,92%), falling down (n: 77, 11,60%), traffic accidents (n: 70.10,54%) and swallowing foreign object (n: 63, 9,49%) cases. When the type of the cases are assessed considering the gender, it is seen that burn comes first in the girls with 39,55% and in boys with 27,87%.Conclusion: Accidents constitute a major part of the preventable health problems in childhood. The injuries that occur as a result of such accidents and have a forensic characteristic happen generally in consequence of home accidents. In order to prevent the children accidents, taking necessary security measures in the living spaces is seen as an effective method to decrease the risks of accident.Keywords: Forensic case, Child, Accident, Precaution.
Keywords: forensic case; child; accident; precaution